TAX RELATIONS AND COMPETENCE DIALECTIC BASIS OF DEVELOPMENT (Global Economic Review: Journal of Economics, Policy, and Business Development, 2025)
This article discusses the theoretical and practical nature of tax capacity and its role in economic development. The content and nature of tax capacity, their interdependence and connections in the system of market relations are highlighted. The article explains the development of tax relations, their modification and the formation of new types of taxes with their impact on economic processes.